A new test for normality and independence - Ejsmont, Wiktor (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
In this paper, a new test of normality and independence is proposed. This test is designed through a multivariate empirical characteristic by considering a result form [Ejsmont 2016]
Didactics of Mathematics, 2017, Nr 14 (18), s. 27-31
Keywords: test; normal distribution; characterization problems